2011
DOI: 10.1177/1352458511417481
|View full text |Cite
|
Sign up to set email alerts
|

Escalation to natalizumab or switching among immunomodulators in relapsing multiple sclerosis

Abstract: We suggest that an escalation to natalizumab is more effective than switching among immunomodulators in RRMS patients who failed a first-line treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 38 publications
3
83
0
7
Order By: Relevance
“…The efficacy advantage of natalizumab compared to BRACE treatments in this study is consistent with other studies comparing these treatment options in patients who switched treatment. 23,30,31 As the population here was wholly treatment-naive, our results extend these findings to potentially inform first-line treatment decisions in clinical practice. Several studies suggest that use of high efficacy treatments earlier in disease course or earlier in treatment sequence could improve long-term patient outcomes.…”
Section: Discussionsupporting
confidence: 64%
“…The efficacy advantage of natalizumab compared to BRACE treatments in this study is consistent with other studies comparing these treatment options in patients who switched treatment. 23,30,31 As the population here was wholly treatment-naive, our results extend these findings to potentially inform first-line treatment decisions in clinical practice. Several studies suggest that use of high efficacy treatments earlier in disease course or earlier in treatment sequence could improve long-term patient outcomes.…”
Section: Discussionsupporting
confidence: 64%
“…Subgroup B comprised patients who had received IFNb in the year before study entry, had at least one relapse in the year before study entry, and had at least either one gadolinium-enhancing T1 lesion or nine T2 lesions at baseline. **P < 0.01, ***P < 0.001 versus placebo, † † † who had an insufficient response to previous treatment with IFNb or GA; the results of these are summarized in Table 1 [13,[40][41][42][43][44][45]. The quality of evidence from these studies is limited by the lack of a control group, and most of them are also retrospective.…”
Section: Natalizumabmentioning
confidence: 99%
“…interferon beta [IFN-β], glatiramer acetate [GA]) is associated with significantly better disease control (fewer relapses, less disease progression as measured by EDSS, and fewer new MRI lesions) compared with switching to another injectable DMT. 7,8 Furthermore, a propensity-matched analysis of the MSBase registry showed that patients who switched to natalizumab after failure of IFN-β or GA had lower relapse rates than those who switched to fingolimod (ARR decreased from 1.5 to 0.2 with natalizumab, from 1.3 to 0.4 with fingolimod; 50% relative postswitch difference in relapse hazard [p = 0.002]). 9 In a recently published analysis, treatment with natalizumab has also been shown to be associated with significantly faster recovery from a relapse compared with placebo (55% and 67% increased probability of 12-week confirmed recovery in patients with an increase in EDSS of ≥0.5 or ≥1.0 during relapse, respectively).…”
Section: Update On Efficacy and Safety Evidence With Natalizumab In Msmentioning
confidence: 99%